The level of evidence of medical marijuana use for treating disabilities: a scoping review. Issue 9 (23rd April 2020) - Stetten, Nichole; Pomeranz, Jamie; Moorhouse, Michael; Yurasek, Ali; Blue, Amy V.
Abstract: Purpose : Twenty-nine states have bypassed federal regulations by legalizing marijuana (MJ) either medicinally, recreationally or both. The FDA states that there is no empirical evidence that MJ is effective to treat these disorders. With over a billion individuals living with a disability across the globe, it is crucial to fully research the efficaciousness and safety of medical MJ to treat this population. The purpose to present the results of a scoping review of studies focused on the levels of evidence currently available on medical MJ's efficacy in treatment across a large range of disabilities. Methods : Databases were searched for research articles on the current level of evidence to support medical MJ use among people with disabilities. Results : Forty-one peer reviewed articles met the inclusion criteria. Articles focused on attention deficit hyperactivity disorder, post-traumatic stress disorder, depression, schizophrenia, spinal cord injury, multiple sclerosis/movement disorders, fibromyalgia, epilepsy, with some that focused on multiple disabilities. Conclusions : The level of evidence for the use of medical MJ among people with disabilities varies greatly, and has a clear lack of methodologically sound studies. Overall, medical MJ does not improve the level of functioning, but it may improve the overall quality of life for people with disabilities. Implications for Rehabilitation: Epilepsy can be a disabling chronic disorder which not only impacts physically but can restricts quality of life. Quality of life is diminished even more with treatment resistant epilepsy. Chronic pain is the leading cause of disability and is the most common cause of long-term disability. There is sufficient evidence that medical marijuana is effective in treating epileptic seizures and chronic pain. Medical marijuana may improve the level of functioning and quality of life for individuals with certain disabilities.